2012
DOI: 10.1002/app.36635
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the liquid absorption behavior of nonwovens on their material and structural characteristics: Modeling and experiments

Abstract: Nonwovens are widely used as liquid absorbent products. Baby diapers, sanitary napkins, adult incontinence pads, oil sorbents, wet wipes, and wound dressings, to name a few, are excellent examples of the use of nonwovens as absorbent media. The performance of nonwoven absorbent media is determined by its liquid absorption behavior, which is characterized by the capacity of absorption and the rate of absorption. In this article, we report on the effects of the physical characteristics of the constituent fibers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In this respect, viscose fibers have a greater ability to absorb water, compared to the polypropylene fibers, thanks to free hydroxyl groups (contained in the amorphous areas, as well as on the surface of the crystals) that are able to interact with molecules of water . Also, Das and associates observed that the total capacity of absorption and the rate of absorption increased with increasing porosity . From Figure and Table , it is possible to notice that water absorptive capacity was highest for the sample with the highest total porosity (Sample A) and decreased with the decrease of the porosity of investigated samples.…”
Section: Resultsmentioning
confidence: 75%
“…In this respect, viscose fibers have a greater ability to absorb water, compared to the polypropylene fibers, thanks to free hydroxyl groups (contained in the amorphous areas, as well as on the surface of the crystals) that are able to interact with molecules of water . Also, Das and associates observed that the total capacity of absorption and the rate of absorption increased with increasing porosity . From Figure and Table , it is possible to notice that water absorptive capacity was highest for the sample with the highest total porosity (Sample A) and decreased with the decrease of the porosity of investigated samples.…”
Section: Resultsmentioning
confidence: 75%
“…The dry fabric should absorb liquids and the wet wipe should be tolerant to lotions and keep applied liquid in the product until the moment of use and release it for the intended purpose [28]. The phenomena of vertical wicking, absorbency, and liquid spreading are affected by the material (blend ratio), fiber diameter, fiber orientation distribution, thickness, weight, porosity, pore size, its distribution, and tortuosity of the pores [2932]. For the wet wipes, at least a portion of the fibers must have a surface energy that is high enough to allow them to be wetted by the wetting solution [6].…”
Section: Introductionmentioning
confidence: 99%
“…e research by the authors Das, D. et al entitled Liquid Sorption Behavior of Superabsorbent Fiber Based Nonwoven Media from 2013 [10] deals with the absorption of nonwovens from superabsorbent bres. In the last few years, many researches were dealing with the relation between the bre diameter, pore size of the nonwoven fabric and the ability of absorption [11][12][13][14][15][16]. In the last four years, many researches have dealt with nonwoven products for hygiene that contain the super absorbent polymer (SAP) [11][12][13][14][15][16].…”
mentioning
confidence: 99%
“…In the last few years, many researches were dealing with the relation between the bre diameter, pore size of the nonwoven fabric and the ability of absorption [11][12][13][14][15][16]. In the last four years, many researches have dealt with nonwoven products for hygiene that contain the super absorbent polymer (SAP) [11][12][13][14][15][16]. Since its development in the late 1970s and early 1980s, the use of SAP has revolutionised the diaper industry as diaper manufacturers soon began to Tekstilec, 2016, 59(4), 298-310 design diapers that were thinner, more absorbent and comfortable than ever before [17].…”
mentioning
confidence: 99%